Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/jp982444b
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Insights into the Molecular Hydration Process: A Case Study of Crown Ethers

Abstract: Ab initio quantum chemical methods as well as simulation/dynamics programs have been conventionally used for probing the hydration of molecules, an important problem in chemistry and biology. However, very few attempts have as yet been reported for understanding the stepwise patterns in hydration processes at the molecular level. The present work investigates the problem of hydration of the 18-crown-6 (18C6) molecule based on rigorous topography mapping of molecular electrostatic potential (MESP) followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…31 The shifted parallel geometry has EPIC interaction energy of −0.97 kcal/ mol, while for T-shaped it is −0.71 kcal/ mol. ͑2͒, using EPIC program.…”
Section: A Co 2 Homoclusters and The Effect On Asymmetric Stretchingmentioning
confidence: 99%
“…31 The shifted parallel geometry has EPIC interaction energy of −0.97 kcal/ mol, while for T-shaped it is −0.71 kcal/ mol. ͑2͒, using EPIC program.…”
Section: A Co 2 Homoclusters and The Effect On Asymmetric Stretchingmentioning
confidence: 99%
“…21,22 On the other hand, in recent years, hydration of the crown ether molecules and complexes has been also studied by both the theoretical [23][24][25][26][27][28][29][30][31] and experimental [32][33][34][35][36][37] approaches, but most of these studies were in aqueous solution. Studies concerning hydration in the wet-organic solvents for the crown ether system are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction energy is minimized by rotating and translating the guest molecule such that the van der Waals surfaces of the guest and the host do not interpenetrate. The EPIC model was applied successfully to many systems such as DNA base dimers and trimers [86], hydration of crown ether [87] and stacked and H-bonded cytosine dimer [88]. Previous studies performed in our laboratory generally demonstrated striking similarities between the geometries obtained from ab initio and EPIC calculations.…”
Section: Use Of Molecular Electrostatic Potential For Probing Lone Pamentioning
confidence: 79%